Adverse Childhood Experiences and Subjective Cognitive Decline in the US. (April 2022) - Brown, Monique J.; Kaur, Amandeep; James, Titilayo; Avalos, Carlos; Addo, Prince N. O.; Crouch, Elizabeth; Hill, Nikki L.
Objective: The aim of this study was to determine the association between adverse childhood experiences (ACEs) and subjective cognitive decline (SCD) among a representative sample of the adult US population. Methods: Data were obtained from the 2019 Behavioral Risk Factor Surveillance System ( N = 82, 688, ≥45 years). Adverse childhood experiences included sexual, physical/psychological and environmental ACEs, and a score. Multivariable logistic regression was used to determine the association between ACEs and SCD, and SCD-related outcomes. Results: Sexual (adjusted OR (aOR: 2.83; 95% CI: 2.42–3.31)), physical/psychological (aOR: 2.05; 95% CI: 1.83–2.29), and environmental (aOR: 1.94; 95% CI: 1.74–2.16) ACEs were associated with SCD in the past year. There was also a dose-response relationship between ACE score and SCD. Conclusion: ACEs were associated with SCD. Interventions to maximize cognitive health in aging and prevent future cognitive impairment should consider the potential role of ACEs among affected populations.